Intentionality of the Relationship between the Forest Resource Management Organization and its Stakeholders - Jerzy MROWKA (Communications of International Proceedings, 2025)
The motivation for research on the intentionality of relationships between organizations managing forest resources and their stakeholders was a natural consequence of expanding the author's studies on strategies for shaping stakeholder relationships. The main arguments for combining these areas were the author's over 30 years of professional experience in the State Forests and theoretical experience focusing on the management of hybrid organizations established to meet public-economic needs based on the principles of market play. The research results presented in the article complement the rare and fragmentary literature reports referring to the premises that public organizations managing forest resources and their stakeholders follow when establishing and maintaining mutual relationships. These results are beneficial for the practice and science of managing organizations, shaping the natural environment.  Based on a broad review of the literature on stakeholder theory, relationship management, relational rent, strategic management, and management of public entities, an own research tool was developed. It took the form of survey questionnaires, which were sent to 29 groups of identified stakeholders of the State Forests. As a result of the research, 1021 survey questionnaires were received. The aggregated research results allow us to state that some factors implying relationships, like in the case of an "iceberg", are hidden deep beneath the observed surface. Relations between organizations managing forest resources and their stakeholders are characterized by complexity and high dynamics, and the intentionality of the relationship is reflected in the growing needs of their stakeholders in terms of fuller participation, cooperation, partnership, or even participation in power and exercising social control.
Keywords: intentionality of relationships; relational rent; Stakeholders; State Forests; relationships.